Adipokines influence the inflammatory balance in autoimmunity. Issue 2 (October 2015) - Hutcheson, Jack
Highlights Adipose tissue is a rich depot of immune cells and bioactive adipokines. Obesity is associated with the severity of several autoimmune diseases. Several adipokines may provide novel biomarkers for autoimmune diseases.